Postoperative cognitive dysfunction in premenopausal versus postmenopausal women. (3rd March 2020) - Chen, Y.-C.; Sun, W.-Z.
Abstract: Purpose: The study examined postoperative cognitive dysfunction in premenopausal and postmenopausal women undergoing surgery with general anesthesia. Methods: This cross-sectional observational study enrolled 30 premenopausal and 28 postmenopausal patients (age 40–60 years) who did not receive hormone replacement therapy, hysterectomy, or oophorectomy. Patients with no menstrual periods for at least 1 year were defined as postmenopausal. The Tablet-based Symbol Digit Modalities Test (T-SDMT) and the Computerized-Digit Vigilance Test (C-DVT) were conducted prior to surgery and on postoperative days (POD) 1 and 7. Results: Postmenopausal patients had a significantly higher T-SDMT reaction time than premenopausal patients preoperatively and on POD 7. Menopausal groups differed in T-SDMT and C-DVT scores preoperatively and postoperatively, but the difference was no longer significant after adjustment for age. Postmenopausal patients had a significantly higher C-DVT hit-reaction time than premenopausal patients on POD 1 and POD 7. On POD 7, 0% of premenopausal and 10.7% of postmenopausal patients had a worse T-SDMT hit-reaction time than at baseline. Pearson's correlation analysis showed that baseline T-SDMT was significantly correlated with age and postmenopausal years; C-DVT was correlated with menopausal duration. Conclusions: By POD 7, menopause status has no noticeable effect on cognitive function in middle-aged women undergoing general surgery.